2009
DOI: 10.1097/eja.0b013e32832b13a2
|View full text |Cite
|
Sign up to set email alerts
|

Blind intubation device for nasotracheal intubation in 100 oral and maxillofacial surgery patients with anticipated difficult airways: a prospective evaluation

Abstract: We have demonstrated the safe and effective use of the blind intubation device in 100 adult patients with anticipated difficult airways. The overall success rates of the oesophagus airway placement, the light-guiding catheter insertion and nasotracheal intubation over the light-guiding catheter were really satisfied. This technique could improve the success of blind nasal intubation, especially in situations in which fibreoptic equipment was unavailable. However, further studies are still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…After being well lubricated, it could slide into the vocal cords very easily with minor adjustments of the oesophagus airway. 4 Although without direct vision guidance, satisfactory sedation and lack of distortion of sensitive supraglottic structures made our patients feel calm and comfortable during attempts to insert the light-guided catheter into the vocal cord. (4) Previous evidence has suggested that direct tracheal stimulation is the primary cause of the cardiovascular response.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…After being well lubricated, it could slide into the vocal cords very easily with minor adjustments of the oesophagus airway. 4 Although without direct vision guidance, satisfactory sedation and lack of distortion of sensitive supraglottic structures made our patients feel calm and comfortable during attempts to insert the light-guided catheter into the vocal cord. (4) Previous evidence has suggested that direct tracheal stimulation is the primary cause of the cardiovascular response.…”
Section: Discussionmentioning
confidence: 91%
“…A bright glow in the midline at the level of the laryngeal prominence and disappearance at the level of the suprasternal notch indicated that the light-guided catheter had passed through the glottis. 4 Carinal stimulation was avoided by fixation of the light-guided catheter while the light spot disappeared. The battery cell was detached, and the oesophagus airway was removed carefully.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the ventilation hole might be under the glottis and, thus, we pulled the oesophagus airway out slightly. 17,18 A bright, well circumscribed circle of glow in the midline at the level of the laryngeal prominence and disappearance at the level of the suprasternal notch indicated that the lighted catheter had passed through the glottis. 3,8,17,18 Third, the battery cell was detached, and the oesophagus airway was removed carefully.…”
Section: Methodsmentioning
confidence: 99%
“…In the nasotracheal intubation process and management, additional instruments, drugs, and skilled maneuvers are required, and with recent developments in techniques and methods, potential problems or complications arising from the blind introduction of the endotracheal tube into the nasal cavity can be avoided [6][7][8][9]. Therefore, this study aimed to summarize the latest findings with a literature review regarding nasotracheal intubation.…”
mentioning
confidence: 99%